The effect of processing method on the in vitro characteristics of red blood cell products. Issue 4 (9th February 2015) - Hansen, A. L.; Kurach, J. D. R.; Turner, T. R.; Jenkins, C.; Busch, M. P.; Norris, P. J.; Dugger, J.; Tomasulo, P. A.; Devine, D. V.; Acker, J. P.
<x xml:space="preserve">Abstract</x> Background and Objectives While the clinical impact of differences in red blood cell (RBC) component processing methods is unknown, there are concerns they may be confounding variables in studies such as the ongoing 'age of blood' investigations. Here, we compare the in vitro characteristics of red cell concentrates (RCCs) produced by several different processing methods. Materials and Methods Nine processing methods were examined: three apheresis methods (Alyx, MCS+ and Trima), as well as leucoreduced whole blood‐derived RCCs produced by buffy coat and whole blood filtration and non‐leucoreduced RCCs. RCCs were stored in saline–adenine–glucose–mannitol or additive solutions (AS) 1 or 3 for 42 days, with quality tested on day 5 and day 42. Results Many significant product differences were observed both early in and at the end of storage. Mean haemoglobin (Hb) ranged from 52 to 71 g/unit and mean Hct from 59·5 to 64·8%. Most RCC passed regulated quality control criteria according to Canadian Standards Association guidelines, although there were some failures relating to Hb content and residual WBC counts. Conclusion Processing method impacts RCC characteristics throughout storage; better understanding of these differences and reporting of processing method details is critical.